Scenic beauty preferences of Cameron Highlands Malaysia: local versus foreign tourists - Othman, Jamilah (Center for Promoting Ideas (CPI), USA, 2011)
Scenic beauty is an important component of the tourism industry in the highland environment of Malaysia. This paper presents the differences in scenic beauty preferences between local and foreign tourists visiting the Cameron Highlands, using a questionnaire survey (n = 439). The aim of the study was to evaluate the effects of three scenic beauty parameters (natural, land uses, and management activities) on the scenic beauty preferences of both groups. An exploratory field observation was used to determine the relevant management variables that were probably associated with the highland management practices. The Independent Sample t–Test was used to compare the differences in their preferences. The hypotheses stated that foreign tourists were more likely to agree on the effects of management practices on the scenic beauty preferences than were the local tourists. While those hypotheses were not fully supported in this study, results did indicate that there are significant differences in two scenic beauty parameters: natural beauty and management activities. Interestingly, foreign tourists stated higher agreement on the effects of the natural beauty and management activities parameters than did the local tourists. These facts suggest that the foreign tourists were more sensitive to the effects of the current landscape management practices than were the local tourists. Secondly, the results also suggest that the foreign tourists appreciated the natural beauty of the Cameron Highlands more than the local tourists did. Importantly, the findings have implications to the District Council and Land Office of Cameron Highlands, since the agencies can use the information to decide on suitable management practices that benefit the tourism industry here. Good management decisions can help protect and sustain one of the most precious natural resources of the country from becoming exploited and exhausted.